Size assessing of different silica-based materials by asymmetrical flow field flow fractionation: from nanometers to micrometers - L. Sanjuan-Navarro; P. Sanchis-Angulo; Y. Moliner-Martínez; P. Campíns-Falcó (Analytica Chimica Acta, 2026)

Sound intensity-dependent cortical activation: implications of the electrical and vascular activity on auditory intensity - Vanesa Muñoz; Brenda Y. Angulo-Ruiz; Carlos M. Gómez (Cognitive Neurodynamics, 2025)
Recent studies combining electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) have shown promising results linking neural and vascular responses. This study analyzes the topographical effect of auditory stimulus intensity on cortical activation and explores neurovascular coupling between fNIRS hemodynamic signals and auditory-evoked potentials (AEPs), extracted from EEG. Forty healthy volunteers (13 males, 27 females; mean age = 22.27 ± 3.96 years) listened to complex tones of varying intensities (50-, 70-, and 90-dB SPL) across seven frequencies (range of 400–2750 Hz) in blocks of five, while EEG and fNIRS were recorded. PERMANOVA analysis revealed that increasing intensity modulated hemodynamic activity, leading to amplitude changes and enhanced recruitment of auditory and prefrontal cortices. To isolate stimulus-specific activity, Spearman correlations were computed on residuals—components of AEPs and fNIRS responses with individual trends removed. The N1 amplitude increase was correlated with higher superior temporal gyrus (STG) and superior frontal gyrus (SFG) activity, and reduced activity in inferior frontal gyrus (IFG) for the oxygenated hemoglobin (HbO), while the deoxygenated hemoglobin (HbR) was associated with increased activity in one channel near the Supramarginal Gyrus (SMG). P2 amplitude increase was associated with higher activation in SFG and IFG for HbO, while for HbR with the activity in SMG, angular gyrus (AnG), SFG, and IFG. Additionally, internal correlations between fNIRS channels revealed strong associations within auditory and frontal regions. These findings provide insights into existing models of neurovascular coupling by showing how stimulus properties, such as intensity, modulate the relationship between neural activity and vascular responses.

Description of an Enterococcus faecium genotype vanB outbreak in a hospitalization ward - M. Andrés; A. Fajardo; M. C. García; L. Grau; Y. Angulo; V. Marín; V. Plasencia; G. Santillana; E. Jiménez; M. Ballestero (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Neurovascular coupling during auditory stimulation: event-related potentials and fNIRS hemodynamic - Vanesa Muñoz; Manuel Muñoz-Caracuel; Brenda Y. Angulo-Ruiz; Carlos M. Gómez (Brain Structure and Function, 2023)
Intensity-dependent amplitude changes (IDAP) have been extensively studied using event-related potentials (ERPs) and have been linked to several psychiatric disorders. This study aims to explore the application of functional near-infrared spectroscopy (fNIRS) in IDAP paradigms, which related to ERPs could indicate the existence of neurovascular coupling. Thirty-three and thirty-one subjects participated in two experiments, respectively. The first experiment consisted of the presentation of three-tone intensities (77.9 dB, 84.5 dB, and 89.5 dB) lasting 500 ms, each type randomly presented 54 times, while the second experiment consisted of the presentation of five-tone intensities (70.9 dB, 77.9 dB, 84.5 dB, 89.5 dB, and 94.5 dB) in trains of 8 tones lasting 70 ms each tone, the trains were presented 20 times. EEG was used to measure ERP components: N1, P2, and N1–P2 peak-to-peak amplitude. fNIRS allowed the analysis of the hemodynamic activity in the auditory, visual, and prefrontal cortices. The results showed an increase in N1, P2, and N1–P2 peak-to-peak amplitude with auditory intensity. Similarly, oxyhemoglobin and deoxyhemoglobin concentrations showed amplitude increases and decreases, respectively, with auditory intensity in the auditory and prefrontal cortices. Spearman correlation analysis showed a relationship between the left auditory cortex with N1 amplitude, and the right dorsolateral cortex with P2 amplitude, specifically for deoxyhemoglobin concentrations. These findings suggest that there is a brain response to auditory intensity changes that can be obtained by EEG and fNIRS, supporting the neurovascular coupling process. Overall, this study enhances our understanding of fNIRS application in auditory paradigms and highlights its potential as a complementary technique to ERPs.

Linear and Non-linear Analyses of EEG in a Group of ASD Children During Resting State Condition - Brenda Y. Angulo-Ruiz; Francisco J. Ruiz-Martínez; Elena I. Rodríguez-Martínez; Anca Ionescu; David Saldaña; Carlos M. Gómez (Brain Topography, 2023)
This study analyses the spontaneous electroencephalogram (EEG) brain activity of 14 children diagnosed with Autism Spectrum Disorder (ASD) compared to 18 children with normal development, aged 5–11 years. (i) Power Spectral Density (PSD), (ii) variability across trials (coefficient of variation: CV), and (iii) complexity (multiscale entropy: MSE) of the brain signal analysis were computed on the resting state EEG. PSD (0.5–45 Hz) and CV were averaged over different frequency bands (low-delta, delta, theta, alpha, low-beta, high-beta and gamma). MSE were calculated with a coarse-grained procedure on 67 time scales and divided into fine, medium and coarse scales. In addition, significant neurophysiological variables were correlated with behavioral performance data ( Kaufman Brief Intelligence Test (KBIT) and Autism Spectrum Quotient (AQ)). Results show increased PSD fast frequency bands (high-beta and gamma), higher variability (CV) and lower complexity (MSE) in children with ASD when compared to typically developed children. These results suggest a more variable, less complex and, probably, less adaptive neural networks with less capacity to generate optimal responses in ASD children.

Multiscale entropy of ADHD children during resting state condition - Brenda Y. Angulo-Ruiz; Vanesa Muñoz; Elena I. Rodríguez-Martínez; Celia Cabello-Navarro; Carlos M. Gómez (Cognitive Neurodynamics, 2023)
This present study aims to investigate neural mechanisms underlying ADHD compared to healthy children through the analysis of the complexity and the variability of the EEG brain signal using multiscale entropy (MSE), EEG signal standard deviation (SDs), as well as the mean, standard deviation (SDp) and coefficient of variation (CV) of absolute spectral power (PSD). For this purpose, a sample of children diagnosed with attention-deficit/hyperactivity disorder (ADHD) between 6 and 17 years old were selected based on the number of trials and diagnostic agreement, 32 for the open-eyes (OE) experimental condition and 25 children for the close-eyes (CE) experimental condition. Healthy control subjects were age- and gender-matched with the ADHD group. The MSE and SDs of resting-state EEG activity were calculated on 34 time scales using a coarse-grained procedure. In addition, the PSD was averaged in delta, theta, alpha, and beta frequency bands, and its mean, SDp, and CV were calculated. The results show that the MSE changes with age during development, increases as the number of scales increases and has a higher amplitude in controls than in ADHD. The absolute PSD results show CV differences between subjects in low and beta frequency bands, with higher variability values in the ADHD group. All these results suggest an increased EEG variability and reduced complexity in ADHD compared to controls.

Activation-Inhibition dynamics of the oscillatory bursts of the human EEG during resting state. The macroscopic temporal range of few seconds - Carlos M. Gómez; Brenda Y. Angulo-Ruíz; Vanesa Muñoz; Elena I. Rodriguez-Martínez (Cognitive Neurodynamics, 2022)
The ubiquitous brain oscillations occur in bursts of oscillatory activity. The present report tries to define the statistical characteristics of electroencephalographical (EEG) bursts of oscillatory activity during resting state in humans to define (i) the statistical properties of amplitude and duration of oscillatory bursts, (ii) its possible correlation, (iii) its frequency content, and (iv) the presence or not of a fixed threshold to trigger an oscillatory burst. The open eyes EEG recordings of five subjects with no artifacts were selected from a sample of 40 subjects. The recordings were filtered in frequency ranges of 2 Hz wide from 1 to 99 Hz. The analytic Hilbert transform was computed to obtain the amplitude envelopes of oscillatory bursts. The criteria of thresholding and a minimum of three cycles to define an oscillatory burst were imposed. Amplitude and duration parameters were extracted and they showed durations between hundreds of milliseconds and a few seconds, and peak amplitudes showed a unimodal distribution. Both parameters were positively correlated and the oscillatory burst durations were explained by a linear model with the terms peak amplitude and peak amplitude of amplitude envelope time derivative. The frequency content of the amplitude envelope was contained in the 0–2 Hz range. The results suggest the presence of amplitude modulated continuous oscillations in the human EEG during the resting conditions in a broad frequency range, with durations in the range of few seconds and modulated positively by amplitude and negatively by the time derivative of the amplitude envelope suggesting activation-inhibition dynamics. This macroscopic oscillatory network behavior is less pronounced in the low-frequency range (1–3 Hz).

Hereditary Ataxias in Cuba: A Nationwide Epidemiological and Clinical Study in 1001 Patients - Luis Velázquez-Pérez; Jacqueline Medrano-Montero; Roberto Rodríguez-Labrada; Nalia Canales-Ochoa; Jandy Campins Alí; Frank J Carrillo Rodes; Tania Rodríguez Graña; María O. Hernández Oliver; Raul Aguilera Rodríguez; Yennis Domínguez Barrios; Reydenis Torres Vega; Lissi Flores Angulo; et al. (The Cerebellum, 2020)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Sputum induction for the diagnosis of pulmonary tuberculosis: a systematic review and meta-analysis - Y. Gonzalez-Angulo; C. S. Wiysonge; H. Geldenhuys; W. Hanekom; H. Mahomed; G. Hussey; M. Hatherill (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Glycosylation and sorting pathways of lysosomal enzymes in mussel digestive cells - Y. Robledo; I. Marigómez; E. Angulo; M. P. Cajaraville (Cell and Tissue Research, 2006)